Modified DFT-Based Phasor Estimation Algorithms for Numerical Relaying Applications - Silva, K. M.; Nascimento, F. A. O. (IEEE transactions on power delivery, 2018)
In this paper, new modifications of the conventional full-cycle and half-cycle discrete Fourier transform (DFT)-based phasor estimation algorithms are proposed. The key idea is to combine two consecutive outputs of their real and imaginary part filters to eliminate the harmful effect of the decaying dc components on phasor estimation, thereby a new strategy to estimate the exponential term is also reported. The proposed algorithms are compared with other DFT-based algorithms by using both computer-simulated and alternative transients program-generated signals. The obtained results reveal that proposed algorithms present excellent results, even taking into account multiple decaying dc components.